PENGARUH PENGGUNAAN GAME EDUKASI QUIZIZZ TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF TINGKAT TINGGI SISWA SMP - Dewa Nyoman Oka; Ni Nyoman Serma Adi (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
This study aims to determine the Effect of Using the Quizizz Educational Game on Motivation and High-Level Cognitive Learning Outcomes of Junior High School Students. This study is a type of Quasi Experimental research (semi-experimental) because in reality this study cannot fully control external variables that affect the implementation of the experiment. The research design used is nonequivalent control group design. The population in this study were all students in class VII and VIII of SMP Negeri 2 Marga (456 people) and SMP Negeri 4 Kediri (250 people). Meanwhile, the number of samples was 53 people from 2 Marga State Middle School and 56 people from Kediri State Middle School. The sample in each school was divided into two classes, namely the experimental class and the control class. Based on the study, the results showed that the average value of the learning motivation score of students in the experimental class (42.12) was higher than the control class (36.08). The t-test results showed a t value of 3.340 with a p-value of 0.002, indicating that the difference in learning motivation between the experimental and control classes was statistically significant (p-value <0.05). Meanwhile, the average value of students' high-level cognitive learning outcomes in the experimental class (83.31) was also higher than in the control class (81.13). The t-test results showed a t value of 3.136 with a p-value of 0.002, indicating that the difference in cognitive learning outcomes between the experimental and control classes was statistically significant (p-value <0.05). So it can be concluded that the Effect of Using the Quizizz Educational Game has a positive effect on Learning Motivation and High-Level Cognitive Learning Outcomes of Junior High School Students.